Visualization of parasite–host interactions using atmospheric-pressure MALDI mass spectrometry imaging - Wiedemann, Katja Rebecca; Justus Liebig University Giessen (My University, 2025)
Endoparasites completely rely on the host organism to survive, once they entered their host. Though, hosts do not capitulate but try to protect themselves against potential damage induced by the parasite. Taking these two effects together, leads to measurable changes in the composition and lateral distribution of metabolites in host tissue (upon infection). In order to find novel drug targets, further knowledge on such changes is crucial. Using mass spectrometry imaging to investigate host-parasite interactions in vivo in an untargeted fashion whilst maintaining the lateral information of metabolites is a powerful approach. Therefore, two distinct models were studied: Schistosoma-mansoni-egg-containing liver samples of hamsters infected with the blood flukes, and bovine skin tissue, showing cysts formed by the apicomplexan parasite Besnoitia besnoiti.
For both parasite-host systems, characteristic infection markers were found with significant changes in signal intensities.
Additionally, by benefiting from the fact that lateral information is kept during mass spectrometry imaging analysis, the lateral distribution of infection markers was revealed. For some of them, co-localized biological structures were observed in optical images of the analyzed tissues.
During schistosomiasis, Schistosoma mansoni eggs are deposited in the hamster liver, leading to granuloma formation around the eggs. The high lateral resolution of the AP-SMALDI5 AF ion source enabled the unambiguous visualization of both, eggs (100 µm to 200 µm in diameter) and local abundance changes of lipids in granulomatous tissue compared to healthy hepatic tissue. Guided by results obtained with liquid chromatography-tandem mass spectrometry, we observed a substructure in formed granulomas by applying mass spectrometry imaging. For example, ether-phosphatidyl-ethanolamines were mainly found in the outer part of the granulomas. In total, 372 substances were found to be significantly changed due to infection.
In the skin of Besnoitia besnoiti-infected cattle, MS images showed both, enrichment and depletion of several lipid species inside parasite-formed cysts. Due to the high lateral resolution at 2 µm pixel size, some of them were even found to be characteristic for the thin cyst walls. Applying multiple MSI methodologies, cysts were further characterized by on-tissue tandem mass spectrometry as well as 3-dimensional imaging. Overall, 552 ions were found to be altered due to infection.
Overall, gained insights into parasite-host interactions can now be used as starting points for further metabolism studies and also serve as potential drug targets.
Keywords: ddc:540